On estimations of solutions of one convolution type equation - Vynnytskyi, B.V.; Dilnyi, V.M. (Carpathian Mathematical Publications, 2013)
We consider a convolution type equation in a semi-strip for the functions belonging to the Hardy-Smirnov space. Estimations of solutions are obtained in terms of analytic continuation.